ANALISA YURIDIS EFEKTIFITAS REHABILITASI BAGI PENYALAHGUNA NARKOTIKA MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Purnomo, Juwita Sari; Fauzi Yulianis, M Syifa (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2023)
Rehabilitation is a way provided by the government to be able to provide more life opportunities for narcotics abusers. Rehabilitation itself is restoration to the previous (original) position (state, good name), or Rehabilitation can also be interpreted as repairing disabled limbs and so on for individuals (eg hospital patients, disaster victims) so that they become useful human beings and have a place in society, or rehabilitation itself is a process of recovering someone who has a serious illness so that that person is in good physical and psychological condition. Rehabilitation is regulated in Law Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika, that in Indonesia a person who abuses Narcotics is still given the same rights as other people as long as he has carried out a sentence, both imprisonment and rehabilitation. The government has played an active role in carrying out rehabilitation efforts for narcotics abusers. The government must have standards with a pattern of cooperation so that rehabilitation becomes one of the effective efforts in the attack against narcotics.